2017
DOI: 10.1371/journal.pone.0172147
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac iron overload in chronically transfused patients with thalassemia, sickle cell anemia, or myelodysplastic syndrome

Abstract: The risk and clinical significance of cardiac iron overload due to chronic transfusion varies with the underlying disease. Cardiac iron overload shortens the life expectancy of patients with thalassemia, whereas its effect is unclear in those with myelodysplastic syndromes (MDS). In patients with sickle cell anemia (SCA), iron does not seem to deposit quickly in the heart. Our primary objective was to assess through a multicentric study the prevalence of cardiac iron overload, defined as a cardiovascular magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 41 publications
(49 reference statements)
2
41
1
1
Order By: Relevance
“…Short-and long-term effects of the most frequently used AIC treatments (steroids and rituximab) and supportive care measures (transfusions) are well established in various populations. 12,[34][35][36][37] Comparing our AIC cohort to controls, we found that iron overload and steroid-induced late effects including AVN and cataracts were more prevalent. This is likely attributed to the higher need of transfusion support leading to iron overload and prolonged courses of steroids to treat these AICs.…”
Section: Discussionmentioning
confidence: 81%
“…Short-and long-term effects of the most frequently used AIC treatments (steroids and rituximab) and supportive care measures (transfusions) are well established in various populations. 12,[34][35][36][37] Comparing our AIC cohort to controls, we found that iron overload and steroid-induced late effects including AVN and cataracts were more prevalent. This is likely attributed to the higher need of transfusion support leading to iron overload and prolonged courses of steroids to treat these AICs.…”
Section: Discussionmentioning
confidence: 81%
“…A second study also showed that among 41 chronically transfused patients with SCD with a mean age of 22.9 years, none developed a cardiac T2* of less than 20 ms during 2 years of follow-up. 159 In the third study, 6 of 201 patients developed cardiac iron overload; these 6 patients had poor chelation compliance, serum ferritin levels of more than 4600 ng/mL, and elevated liver iron concentrations of more than 22 mg/g (dw). 160 No studies reported iron-induced endocrinopathies or mortality with regard to MRI monitoring of iron overload.…”
Section: Remarksmentioning
confidence: 99%
“…Three observational studies showed an extremely low prevalence of cardiac T2* abnormalities in transfused patients with SCD, and evidence of cardiac iron loading developed only with prolonged elevated liver iron concentration. [158][159][160] One study of 9 chronically transfused pediatric patients with SCD showed no abnormal cardiac T2* 158 ; 4 had ventricular dilatation. A second study also showed that among 41 chronically transfused patients with SCD with a mean age of 22.9 years, none developed a cardiac T2* of less than 20 ms during 2 years of follow-up.…”
Section: Remarksmentioning
confidence: 99%
“…Breakdown of mature red blood cells over time, in the absence of erythropoiesis, results in an accumulation of non‐transferrin‐bound iron (NTBI) once the transferrin‐binding capacity has been exceeded . In turn, the presence of NTBI results in iron deposits in the cells of various organs (including liver, heart, pancreas, endocrine glands, and joints) and the formation of reactive oxygen species . Ultimately, this can lead to symptoms associated with damage to involved organs, such as liver cirrhosis and hepatocellular carcinoma, diabetes mellitus, arthritis, arrhythmias, heart failure, and hypogonadotropic hypogonadism …”
Section: Introductionmentioning
confidence: 99%